(untitled) (Journal of Naval Architecture and Marine Engineering, 2009)
Fe-TiC composites containing varying amounts of TiC particles have been synthesized by casting route. This is achieved by carbothermic reduction of ilmenite ore along with varying amount of steel scrap in a plasma reactor in one step. Three composites containing TiC particles varying from 4 to 9% have been prepared. Microstructures of composites show TiC particles in the matrix of transformed ledeburite (pearlite and cementite). Distribution of TiC particles has been found to be satisfactorily uniform and size varies from 2 to 3 microns. Composite having 9 vol% has shown non-uniform distribution of TiC particles and size variation from 2 to 8 microns. In 9% TiC composites, graphite flakes have also been found. It has also been observed that composite having TiC content greater than 9 % becomes very difficult to cast because of higher viscosity of the melt during pouring. These composites have been characterized by hardness measurement, optical microscopy, FESEM, and XRD. Hardness of these composites has been found to depend on vol.% of TiC and on the nature of the matrix. Slurry erosion test has shown higher erosion resistance in castings with lesser porosity, optimum vol% of TiC, and in the matrix of transformed ledeburite. Presence of graphite in the matrix lowers slurry erosion resistance of the cast composite. Keywords: Fe-TiC composite, Carbothermic reduction, Graphite, Slurry wear. Â Â doi:10.3329/jname.v5i1.1825 Journal of Naval Architecture and Marine Engineering Vol. 5, No.Â 1 (June, 2008) 19-26.